Factors affecting ultimate strength of solid and glulam timber beams - Abu Bakar, Suhaimi; Saleh, Abd Latif; Mohamed, Zainai (Faculty of Civil Engineering, UTM, 2004)
Phenol Resorcinol Formaldehyde is an adhesive commonly used in the fabrication of glued laminated (glulam) timber beams. Although, it has been widely accepted for softwood species, the verification of this type of adhesive for local timbers is not fully established. Four glulam beams and four solid beams were tested in bending in the laboratory. Phenol Resorcinol Formaldehyde was used as an adhesive for glulam beams. The strength of the glulam beam structure was equivalent to solid beam structure. Phenol Resorcinol Formaldehyde was able to provide sufficient bonding and strength for local timbers. The results indicated that the most significant factor influencing the strength of solid beam and glulam beam structure was the density of timber.